The Effect of Brand Image, Product Quality, and Price on Consumer Satisfaction on Eiger Products in East Java - Diah Yulisetiarini; Tatok Endhiarto; Febri Sharenda Akbar; Deasy Wulandari (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the effect of brand image, product quality, and price on consumer satisfaction with Eiger products. The population of this research is Eiger consumers in Jember. The sampling technique in this research is non-probability sampling with the sampling method used is purposive sampling. based on the criteria that is rmale and female respondents aged 18 years and over and respondents who have purchased and used Eiger products in existing stores in the last 1 year. The sample used was 170 respondents. The type of data in this study uses quantitative data. Primary data sources were obtained directly from questionnaires given via google form and secondary data obtained from web topbrand-award.com, idntimes.com, eigeradventure.com, and jemberkab.go.id. The data analysis method used is multiple regression analysis. The results of this study are three analysis results, namely brand image has a significant effect on consumer satisfaction for Eiger products in Jember. Product quality has a significant effect on consumer satisfaction for Eiger products in Jember.